Periadventitial delivery of mesenchymal stem cells improves vascular remodeling and maturation in arteriovenous fistulas - Kilari, Sreenivasulu; DeMartino, Randall R; Nyberg, Scott L; Dean, Patrick G; Colglazier, Jill J; Takahashi, Edwin; Baranwal, Gaurav; Singh, Prabh G; Kane, Jamie; Nitz, Katrin; Lutgens, Esther; Dillon, John J; et al. (Science translational medicine, 2025)
Worldwide, more than 4 million patients with end-stage kidney disease require hemodialysis through an arteriovenous fistula (AVF). AVFs fail because of venous neointimal hyperplasia (VNH) resulting in venous stenosis formation. A phase 1 randomized trial in patients undergoing upper extremity AVF placement was performed to evaluate the safety and efficacy of autologous adipose-derived mesenchymal stem cells (MSCs) in improving AVF function. The mechanism of action by which MSCs exert their beneficial effects was investigated using AVFs created in mice and pigs treated with allogenic MSCs and xenotransplant using patient MSCs in CD1- mice. At a median follow-up of 42 months, patients with MSC-treated AVFs had reduced time to maturation with an increase in the vein diameter compared with controls. AVFs treated with allogenic MSCs in mice and pigs had an increase in M2- and M1-like macrophages with a decrease in VNH. Transcriptomic analysis of AVFs treated with allogenic MSCs in mouse and MSC xenotransplants of patients with successful AVFs showed decreased peroxisome proliferator-activated receptor gamma ( γ) and leptin receptor ( ) and increased latent transforming growth factor-beta-binding protein 2 ( ). PPARγ was reduced in CD68 (+) cells from successful AVFs and allogenic MSC-treated mouse AVFs. Venous stenosis and VNH formation were mitigated in AVFs of mice with γ ablation in immune cells. Conditioned medium from MSCs of responders versus nonresponders had decreased proinflammatory genes, senescence-associated proteins, and monocyte-to-macrophage differentiation induced by phorbol 12-myristate-13-acetate. Periadventitial delivery of MSCs to AVFs promoted positive vascular remodeling through decreased inflammatory responses.